Ethical and Technical Frameworks for Deploying Honeypots in Public Wireless Networks - Diantoro, Karno (Digitus : Journal of Computer Science Applications, 2024)
Public Wireless Local Area Networks (WLANs) in government and public service institutions are highly vulnerable to cyberattacks, yet conventional firewalls and intrusion detection systems (IDS) often fail to provide proactive defense. This study aims to evaluate the effectiveness of honeypot-based security within the WLAN infrastructure of Dinas Perpustakaan dan Kearsipan Kota Pekanbaru. Using an applied experimental design, honeypots were integrated with Snort IDS and visualized through Honeymap to capture attacker behavior, detect anomalies, and benchmark detection performance. The results show that honeypots reduced detection latency, lowered false positives, and improved accuracy in identifying port scanning and brute force attacks compared to standard firewalls. Additionally, Honeymap enabled geographic analysis of attack origins, enhancing situational awareness. The findings highlight not only the technical benefits but also ethical challenges, particularly regarding user privacy and informed consent. This research recommends that public institutions adopt clear governance frameworks, ensure regular staff training, and maintain continuous system updates to sustain honeypot effectiveness. Strategically deployed, honeypots can strengthen cybersecurity readiness and inform policy development in public network environments.